Analysis of Spinal Posture With Three-Dimensional Ultrasonic System in Patients With Ankylosing Spondylitis - Hakan Sercan KURTOĞLU,; Filiz TUNA,; Hakan TUNA,; Enis ULUÇAM,; Nurettin TAŞTEKİN,; Murat BİRTANE, (Archives of Rheumatology, 2019)
Objectives: This study aims to investigate the relationship between postural changes detected in ankylosing spondylitis (AS) vertebrae and clinical and demographic characteristics of patients using a three-dimensional ultrasonic system. Patients and methods: A total of 44 AS patients (36 males, 8 females; mean age 39.1±9.8 years; range, 18 to 63 years) and 44 healthy volunteers (36 males, 8 females; mean age 38.4±9.4 years; range, 18 to 65 years) were included. Clinical, demographic, and laboratory data were recorded. Spinal posture analysis was performed using a Zebris CMS20 three-dimensional ultrasonic system. Results: Thoracic kyphosis angle was significantly higher in the AS group (45.4±12.8°) than in the control group (36.9±7.7°) (p=0.001). Lumbar lordosis angle was significantly lower in the AS group (20.7±10.6°) than in the control group (28±8.2°) (p=0.002). There were no significant differences in total trunk inclination or sacral angles (p>0.05). Increase in thoracolumbar length at maximum spinal flexion and decrease in thoracolumbar length at maximum spinal extension were significantly lower in the AS group (p<0.05). A negative correlation was found between the thoracic kyphosis angle and length increase in spine flexure as well as chest expansion. Thoracic kyphosis angle had a statistically significantly positive correlation with age at onset of symptoms and tragus-wall distance (p<0.05). Conclusion: Significant changes were observed in spinal posture in patients with AS. In addition, significant correlations were found between dynamic postural changes and spinal mobility. We think that postural evaluation and follow-up should be carried out with other parameters. Awareness of AS patients about postural changes should be increased, and proper exercise treatment should be applied.